H5+ converter: A bidirectional AC-DC converter with DC-fault-blocking and self-pre-charge capabilities - Wang,Y; Li,Y; Junyent,Ferre A; Kim,M (IEEE Transactions on Power Electronics, 2019)
A pulse-width-modulation (PWM) bidirectional ac-dc converter (i.e., active rectifier) with dc-faultblocking and self-pre-charge capabilities is proposed in this paper for low-voltage dc (LVDC) applications. The proposed converter, which is named as ”H5 + converter”, consists of an H4 bridge, a bidirectional switch, and a transient-voltage-surge (TVS) diode. The bidirectional switch and the TVS diode enable the dc-fault blocking and dc-bus self-pre-charge, while preserving the low common mode voltage noise and low leakage current of the converter. Additionally, the proposed H5+ converter has advanced features under a dc-side short circuit fault, such as fault diagnosis and fault recovery. Operation principles of the proposed converter are presented and analyzed. A down scaled prototype is built. Experiment results are shown and analyzed, including steady-state waveforms, common-mode performance, start-up dynamics, as well as dc fault blocking, fault diagnosis, and fault recovery. Moreover, the proposed converter is compared with other two dc-fault blocking converters for LVDC applications, in terms of converter capabilities, required devices, and power switch losses.